A poorly soluble drug nanocrystal composition and a method for preparing the same
Patent Information
- Application Number
- CN202611241141.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0012]综上,现有技术尚未能同时解决“稳定剂吸附力弱导致长期稳定性差、载药量与稳定性难以兼顾、单一工艺存在固有缺陷、缺乏pH响应与渗透促进功能、固态化不可逆团聚”五大技术瓶颈
[0057]1、离子对源头修饰,从根本提升稳定剂锚定强度与物理稳定性
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of pharmaceutical formulation technology, specifically relating to a nanocrystalline composition containing a poorly soluble drug and a hydrophobic ion pair complex, and a method for preparing this composition by wet media milling combined with spray freeze-drying. More specifically, this invention relates to a poorly soluble drug nanocrystalline solid composition prepared based on hydrophobic ion pair modification, a ternary functional composite stabilizing system, and a synergistic process of antisolvent precipitation-gradient high-pressure homogenization-short-range media milling, exhibiting pH-responsive enteric release, enhanced intestinal permeability, high drug loading, and excellent long-term stability. Background Technology
[0002] In new drug development and clinical application, the low oral absorption efficiency of poorly soluble drugs has long been a core challenge in the field of pharmaceutics. According to statistics, about 40% of marketed drugs and as many as 90% of drug candidates under investigation belong to Biopharmaceutics Classification System (BCS) Class II or IV drugs. Their poor water solubility and slow dissolution rate result in low bioavailability after oral administration and large individual differences, which seriously restricts the realization of clinical efficacy.
[0003] Nanocrystal technology is one of the most promising formulation technologies for improving the dissolution of poorly soluble drugs. Its core principle is to reduce the particle size of drug particles to the nanoscale, thereby significantly increasing the specific surface area and improving the dissolution rate and saturated solubility. According to the classic Noyes-Whitney dissolution rate equation:
[0004]
[0005] In the formula, For dissolution rate, The drug diffusion coefficient, This refers to the specific surface area of the drug particles. The thickness of the diffusion layer, For drug saturation solubility, The concentration of the bulk solution is [value missing]. The increased specific surface area resulting from smaller particle size can directly improve the dissolution rate. Furthermore, nanocrystals have high drug loading capacity, require less excipients, and are easy to scale up industrially, thus attracting widespread attention in the industry.
[0006] Currently, the preparation methods for drug nanocrystals are mainly divided into two categories: "top-down" and "bottom-up." Top-down methods are represented by media milling and high-pressure homogenization. Wet media milling is simple to operate and applicable to a wide range of drugs, but it carries the risk of media wear and tear, introducing impurities and contamination. Furthermore, prolonged milling can lead to drug crystal transformation and chemical degradation. High-pressure homogenization produces high-purity products without media contamination, but typically requires dozens of cycles to achieve the target particle size, resulting in high energy consumption, low production efficiency, and limited effectiveness for pulverizing high-hardness drugs. Bottom-up methods are represented by anti-solvent precipitation, which is simple to operate and fast, but the resulting particles are prone to agglomeration, have a wide particle size distribution, poor batch-to-batch reproducibility, and insufficient physical stability. Each single preparation process has inherent defects, making it difficult to simultaneously meet the multiple requirements of uniform particle size, high purity, high efficiency, and good stability.
[0007] Stabilizers are crucial in determining the physical stability of nanocrystals. Current technologies often employ single surfactants or polymers as stabilizers, resulting in limited stabilization mechanisms: ionic surfactants rely solely on electrostatic repulsion, offering limited inhibition of Ostwald ripening during storage; polymer stabilizers rely solely on steric hindrance, leading to poor initial dispersion and particle aggregation during preparation. To improve stability, current research has attempted to combine binary stabilizers, but this still hasn't broken through the two-dimensional stabilization framework of "electrostatic + steric hindrance." Furthermore, the stabilizer's affinity for the drug crystal surface is mostly physical adsorption, resulting in weak adhesion and easy desorption during long-term storage, leading to particle size growth. According to the Lifshitz-Slyozov-Wagner (LSW) Ostwald ripening theory:
[0008]
[0009] In the formula, Let be the average particle size at time t. The initial average particle size, For solid-liquid interfacial tension, The saturation solubility of bulk crystals. The diffusion coefficient of drug molecules in the medium. The molar volume of the drug. The gas constant is... This refers to the thermodynamic temperature. Conventional physically adsorbed stabilizers cannot effectively reduce interfacial tension and molecular diffusion rate, thus making it difficult to effectively inhibit ripening over a long period.
[0010] For addressing the issue of weak stabilizer adsorption, hydrophobic ion pairing technology is a potential solution. By combining ionizable drugs with hydrophobic counterions of opposite charge, the hydrophobicity of the drug surface can be significantly improved, enhancing its interaction with amphiphilic polymers. However, current research primarily focuses on using hydrophobic ion pairs to enhance drug loading in carrier systems such as micelles and liposomes, and has not yet been systematically applied to the stabilization design of nanocrystals, let alone combined with functional excipients such as pH-responsive stabilizers and penetration enhancers to achieve multidimensional improvements in formulation performance.
[0011] Furthermore, existing nanocrystalline formulations often lack active targeting and absorption-enhancing functions. Most nanocrystals are released uniformly throughout the gastrointestinal tract, offering little protection against drugs unstable in gastric acid or those that irritate the stomach, and failing to achieve targeted release into the intestinal tract. For BCS Class IV drugs, simply improving solubility cannot overcome the bottleneck of poor permeability, resulting in limited improvements in bioavailability. Simultaneously, nanocrystalline suspensions are thermodynamically unstable, prone to aggregation and crystal transformation during long-term storage, requiring solidification into a solid formulation. Conventional spray drying at high temperatures easily leads to drug degradation and particle agglomeration, while ordinary tray freeze-drying has a long cycle, is prone to collapse, and results in a significant increase in particle size after redispersement, losing the nano-effect. Although spray freeze-drying technology can improve redispersibility to some extent, existing protectant systems are simply designed and not optimized for the surface characteristics of ionic nanocrystals, leaving room for improvement in protection efficiency.
[0012] In summary, current technologies have not yet been able to simultaneously solve the five major technical bottlenecks: poor long-term stability due to weak stabilizer adsorption, difficulty in balancing drug loading and stability, inherent defects in single processes, lack of pH response and penetration-promoting functions, and irreversible agglomeration during solidification. Developing a poorly soluble drug nanocrystal composition that combines high stability, high drug loading, high bioavailability, and industrial feasibility remains of significant clinical and economic value. Summary of the Invention
[0013] To address the shortcomings of existing technologies, the present invention aims to provide a poorly soluble drug nanocrystalline composition and its preparation method. This composition enhances the anchoring effect of the stabilizer at the molecular level by pre-constructing a drug-hydrophobic ion pair complex, achieves multiple stabilizations and pH-responsive release by combining a ternary functional composite stabilizer, and synergistically improves intestinal absorption with a composite penetration enhancer. The preparation method employs a three-stage synergistic process of antisolvent precipitation, gradient high-pressure homogenization, and short-pathway media milling, combined with a ternary composite protectant and spray freeze-drying technology, to achieve efficient, low-impurity, and highly reproducible industrial preparation. The final product is a poorly soluble drug nanocrystalline composition with small particle size, narrow distribution, high drug loading, excellent long-term stability, and significantly improved oral bioavailability, overcoming many technical bottlenecks in existing technologies.
[0014] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:
[0015] (a) A poorly soluble drug nanocrystal composition
[0016] The composition comprises the following components in parts by dry weight:
[0017] 1. Hydrophobic ion pair complex: 30-60 parts
[0018] The hydrophobic ion-pair complex is formed by the combination of a poorly soluble drug and a hydrophobic ion-pair reagent through ionic bonds, with a molar ratio of 1:(0.5~1.5), preferably 1:(0.8~1.2).
[0019] Furthermore, the poorly soluble drug is a Class II or Class IV drug according to the Biopharmaceutics Classification System (BCS), including a weakly basic drug containing a protonable basic group or a weakly acidic drug containing a deprotonable acidic group. The weakly basic drug is selected from any one of itraconazole, ketoconazole, posaconazole, carvedilol, cinnarizine, loratadine, aprepitant, rilpivirine, and atorvaquinone; the weakly acidic drug is selected from any one of celecoxib, diclofenac, indomethacin, ibuprofen, furosemide, and naproxen.
[0020] Furthermore, the hydrophobic ion-pairing reagent is selected according to the charge properties of the drug: for weakly basic drugs, a negatively charged hydrophobic organic acid and its pharmaceutical salt are selected, chosen from any one or more combinations of cholic acid, deoxycholic acid, taurideoxycholic acid, glycodeoxycholic acid, sodium dodecyl sulfate, stearic acid, and oleic acid; for weakly acidic drugs, a positively charged hydrophobic organic base and its pharmaceutical salt are selected, chosen from any one or more combinations of cetrimonium bromide, arginine dodecyl ester, and choline stearate.
[0021] 2. Ternary functional composite stabilizer: 10-35 parts
[0022] The ternary functional composite stabilizer is composed of an amphiphilic block copolymer, an enteric cellulose derivative, and a functional nonionic surfactant in a mass ratio of 1:(0.3~1):(0.2~0.5).
[0023] Furthermore, the amphiphilic block copolymer is a polyvinyl caprolactam-polyvinyl acetate-polyethylene glycol graft copolymer (Soluplus), in which the hydrophobic blocks are anchored on the surface of the hydrophobic ion pair complex crystal through hydrophobic interactions, and the hydrophilic polyethylene glycol chains extend into the aqueous phase to form a thick hydration layer, providing strong steric stabilization.
[0024] Furthermore, the enteric-coated cellulose derivative is selected from any one or a combination of two of hydroxypropyl methylcellulose phthalate (HPMCP, such as HP-50, HP-55) and hydroxypropyl methylcellulose acetate succinate (HPMCAS, such as LF, MF, HF). The enteric-coated cellulose derivative remains insoluble in an acidic environment with pH < 5.5, forming a dense polymer film on the surface of the nanocrystals to prevent drug release in gastric acid; in an intestinal environment with pH ≥ 6.0, the carboxyl groups dissociate, causing the polymer to swell and dissolve, rapidly releasing the nanocrystals and achieving targeted intestinal release.
[0025] Furthermore, the functional nonionic surfactant is vitamin E polyethylene glycol succinate (TPGS). TPGS is embedded in the gaps of the stabilizer adsorption layer, improving the density and mechanical strength of the interfacial membrane, while inhibiting the efflux of P-glycoprotein (P-gp) from intestinal epithelial cells, reducing drug efflux and improving bioavailability.
[0026] 3. Compound penetration enhancer: 2-8 parts
[0027] The composite penetration enhancer is composed of basic amino acids and medium-chain fatty acid monoglycerides in a mass ratio of (2~4):1.
[0028] Furthermore, the basic amino acid is selected from any one of L-arginine, L-lysine, and L-histidine, preferably L-arginine. L-arginine carries a positive charge in the weakly alkaline environment of the intestine and can interact with negatively charged sites on the surface of intestinal epithelial cell membranes, temporarily opening tight junctions between cells and promoting bypass drug transport; at the same time, it can also act as a precursor of nitric oxide (NO), improving local intestinal microcirculation and indirectly promoting drug absorption.
[0029] Furthermore, the medium-chain fatty acid monoglyceride is glycerol monolaurate, which can improve the efficiency of drug transcellular transport by disrupting the ordered structure of the cell membrane lipid bilayer, and synergistically exert a penetration-promoting effect with basic amino acids.
[0030] 4. Ternary composite freeze-drying protectant: 20-50 parts
[0031] The ternary composite freeze-drying protectant is composed of trehalose, mannitol, and glycine in a mass ratio of (2~4):(1~2):(0.5~1).
[0032] Furthermore, the trehalose is a non-reducing disaccharide with a high glass transition temperature. During the freeze-drying and dehydration process, it can form hydrogen bonds with polar groups on the surface of drug particles through the "water substitution hypothesis," thereby maintaining the particle dispersion state and inhibiting aggregation.
[0033] Furthermore, the mannitol is a crystalline polyol that can form a rigid framework structure during freeze-drying, giving the freeze-dried cake a good appearance and mechanical strength, preventing collapse, and accelerating the reconstitution process.
[0034] Furthermore, the glycine is an amphoteric amino acid that can form a strong hydrogen bond network with trehalose, enhancing the stability of the glassy matrix. At the same time, it can be adsorbed onto the surface of drug particles through charge interaction, further preventing contact fusion between particles.
[0035] 5. Other pharmaceutically acceptable excipients: 0-5 parts
[0036] It includes one or more of pH adjusters, antioxidants, and preservatives, and the dosage is the usual dosage for formulation.
[0037] The nanocrystalline composition is in the form of a solid powder. After reconstitution, the average particle size of the nanocrystals is 80~220nm, the polydispersity index (PDI) is ≤0.20, and the absolute value of the zeta potential is ≥30mV.
[0038] (II) A method for preparing the above-mentioned poorly soluble drug nanocrystal composition.
[0039] Includes the following steps:
[0040] Step 1: Preparation of hydrophobic ion pair complexes
[0041] Poorly soluble drugs are dissolved in organic solvents to obtain drug-organic solutions with a concentration of 5–30 mg / mL. Hydrophobic ion-pairing reagents are dissolved in water or a water-organic mixed solvent to obtain ion-pairing reagent solutions with a concentration of 10–50 mg / mL. Under stirring conditions, the ion-pairing reagent solution is slowly added dropwise to the drug-organic solution. After the addition is complete, the pH of the system is adjusted to the optimal salt-forming pH of the drug and ion-pairing reagent with dilute hydrochloric acid or dilute sodium hydroxide solution. The reaction is continued with stirring in a water bath at 30–45 °C for 1–3 h. After the reaction is complete, the organic solvent is removed by rotary evaporation under reduced pressure. The remaining suspension is pre-frozen and then freeze-dried, or directly spray-dried, to obtain a loose hydrophobic ion-pair complex powder.
[0042] Furthermore, the organic solvent is selected from any one or a mixture of two of the following: dichloromethane, anhydrous ethanol, methanol, acetone, and tetrahydrofuran.
[0043] Step 2: Preparation of coarse nanocrystalline suspension by antisolvent precipitation and pre-dispersion
[0044] The hydrophobic ion-pair complex powder obtained in step 1 was dissolved in a good solvent to obtain a complex organic solution with a concentration of 10-60 mg / mL, which was used as the organic phase. The ternary functional composite stabilizer and composite penetration enhancer were added to the aqueous phase medium and stirred until completely dissolved to obtain an aqueous stabilizer solution, which was used as the aqueous phase. The aqueous phase was placed in a low-temperature water bath and the temperature was controlled at 4-15℃. Under magnetic stirring at 800-2000 rpm, the organic phase was rapidly injected into the aqueous phase at a rate of 5-20 mL / min. After the injection was completed, stirring was continued for 10-30 min to obtain a coarse nanocrystal suspension.
[0045] Furthermore, the volume ratio of the organic phase to the aqueous phase is 1:(5~15); the aqueous phase medium is any one of purified water, phosphate buffer, and acetate buffer.
[0046] Step 3: Gradient high-pressure homogenization and refinement
[0047] The coarse nanocrystalline suspension obtained in step 2 was transferred to a high-pressure homogenizer and subjected to gradient high-pressure homogenization in a two-stage homogenization mode: the first-stage homogenization pressure was 600~1200 bar, and the second-stage homogenization pressure was 10%~15% of the first-stage pressure. The homogenization was repeated 5~12 times to obtain a refined nanocrystalline suspension.
[0048] Preferably, a gradient pressurization strategy is adopted: first, homogenize 2 to 4 times under low pressure of 500 to 700 bar to initially break up large particle aggregates; then, homogenize 3 to 8 times under high pressure of 800 to 1200 bar to further refine the particle size and narrow the distribution.
[0049] Step 4: Short-range media grinding and polishing (optional step)
[0050] For drugs with high crystal hardness and particle size that is difficult to further refine through high-pressure homogenization, the refined nanocrystalline suspension obtained in step 3 is transferred to a horizontal wet media mill for short-path polishing: zirconia grinding beads with a diameter of 0.1~0.3 mm are filled, with a filling rate of 50%~65% of the grinding chamber volume; the grinding speed is set to 2000~3000 rpm, the grinding temperature is controlled at 5~25℃, and the grinding time is 15~30 min; during the grinding process, an inert gas (nitrogen or argon) is introduced above the liquid surface for protection to prevent drug oxidation and degradation. After grinding, the grinding media is filtered out to obtain the refined nanocrystalline suspension.
[0051] Step 5: Spray freeze drying and curing
[0052] Add the prescribed amount of ternary composite lyophilization protectant to the nanocrystalline suspension obtained in step 3 or 4, stir until completely dissolved, and remove insoluble impurities by filtering through a 0.45 μm microporous membrane to obtain the suspension to be dried. Atomize the suspension through a dual-fluid nozzle and spray it into a freezing chamber filled with liquid nitrogen vapor, where it is instantly frozen to form drug-containing micro-frozen particles. Collect the frozen particles and transfer them to a vacuum freeze dryer for sublimation drying.
[0053] First drying stage: shelf temperature -35~-20℃, vacuum degree 10~30Pa, drying time 12~36h, until ice crystals completely sublimate;
[0054] Secondary drying stage: The shelf temperature is gradually increased to 10-25℃ at a rate of 2-5℃ / h, the vacuum degree is 5-15Pa, and the drying time is 4-10h to remove residual bound water; after drying, the material is discharged, sealed and packaged to obtain a solid poorly soluble drug nanocrystal composition.
[0055] Furthermore, the process parameters for spray freeze drying are: feed rate 2~10mL / min, atomizing gas pressure 0.15~0.3MPa, and refrigerant temperature -120~-196℃.
[0056] Compared with the prior art, the present invention has the following outstanding advantages:
[0057] 1. Ion-based source modification fundamentally enhances the anchoring strength and physical stability of stabilizers.
[0058] This invention pre-forms an ion-pair complex between a poorly soluble drug and a hydrophobic ion-pairing reagent, significantly improving the hydrophobicity of the drug crystal surface and greatly enhancing the adsorption affinity of the hydrophobic blocks of the amphiphilic polymer on the crystal surface. This reduces the probability of stabilizer desorption during storage, fundamentally inhibiting Ostwald ripening and particle aggregation. The strong adsorption effect of the stabilizer significantly reduces the solid-liquid interfacial tension (gamma), while the dense adsorption layer reduces the surface diffusion rate of drug molecules, thereby significantly slowing down the particle size growth rate. Accelerated stability tests show that the nanocrystals of this invention, after being stored at 40°C and 75% relative humidity for 6 months, exhibit a particle size growth rate of less than 10%, far superior to conventional physically adsorbed stabilized nanocrystal systems.
[0059] 2. The synergistic effect of the ternary functional stabilizers achieves multiple stabilizations and pH-responsive controlled release in one integrated system.
[0060] The ternary stable system of "amphiphilic block copolymer-enteric cellulose derivative-functional surfactant" constructed in this invention exerts its effects through a triple mechanism. According to the extended DLVO theory, the total interaction energy between nanoparticles is:
[0061]
[0062] In the formula, The total interaction energy, To attract energy for Van der Waals, It is electrostatic repulsion energy. This represents the steric hindrance energy. In this system, the enteric cellulose derivative provides part of the electrostatic repulsion energy. Soluplus's long polyethylene glycol chains provide strong steric hindrance. TPGS filling the interface defects further enhances the steric hindrance strength, and the synergistic effect of the three factors significantly increases the total repulsive energy, effectively preventing particle aggregation. At the same time, enteric cellulose endows the system with pH-responsive release characteristics. In gastric acid (pH 1.2), the cumulative release rate is less than 5% in 2 hours, effectively avoiding drug irritation to the gastric mucosa and degradation by gastric acid; after entering the intestine (pH 6.8), the cumulative release rate reaches more than 90% within 30 minutes, achieving precise intestinal targeted release.
[0063] 3. A three-stage synergistic preparation process that balances particle size uniformity, product purity, and production efficiency.
[0064] This invention innovatively integrates a three-stage process of antisolvent precipitation, gradient high-pressure homogenization, and short-path media grinding, leveraging their complementary advantages: antisolvent precipitation rapidly prepares submicron-sized coarse crystals, significantly reducing energy consumption and cycle count in subsequent homogenization; gradient high-pressure homogenization efficiently refines particle size without the risk of media contamination; and short-path media grinding and polishing are only applied to high-hardness drugs, shortening grinding time by more than 70% compared to traditional processes and greatly reducing the risk of impurities introduced by grinding media wear and shedding. Compared to single high-pressure homogenization, this process reduces cycle count by 60% and increases production efficiency by more than 3 times; compared to single-media grinding, the product purity is higher, with batch-to-batch RSD less than 4%, and significantly improved reproducibility. The final nanocrystals have an average particle size of 80~220nm, PDI≤0.20, narrow and uniform particle size distribution, significantly increased specific surface area, and a significantly improved dissolution rate.
[0065] 4. Dual penetration-enhancing mechanism significantly improves oral bioavailability.
[0066] This invention introduces a composite permeation enhancer consisting of basic amino acids and medium-chain fatty acid monoglycerides, combined with the P-gp inhibition of TPGS, forming a triple absorption synergistic mechanism: L-arginine temporarily opens tight junctions between cells, promoting bypass transport; glycerol monolaurate disrupts the lipid structure of cell membranes, promoting transcellular transport; and TPGS inhibits P-gp efflux, reducing drug loss. The synergistic effect of these three components increases the apparent permeability coefficient of the drug by more than 8 times, and the oral bioavailability in rats is 5-8 times that of the active pharmaceutical ingredient, significantly superior to conventional nanocrystals that rely solely on particle size reduction.
[0067] 5. Ternary composite freeze-drying protectant enables fully reversible solid-state redispersion.
[0068] This invention employs a ternary freeze-drying protection system of trehalose-mannitol-glycine, combined with the instantaneous freeze-curing technology of spray freeze-drying, to form a uniform and porous glassy matrix around nanocrystalline particles. Trehalose acts as a water substitute to maintain the stability of the particle interface, mannitol forms a rigid framework to prevent collapse, and glycine strengthens the hydrogen bond network and blocks particle contact. The synergistic effect of these three components results in an average particle size increase of less than 8% after reconstitution of the solid composition, with a PDI below 0.20, almost completely restoring the original state of the liquid nanocrystals, far superior to single or binary protective agent systems. Simultaneously, spray freeze-drying avoids the high-temperature damage of conventional spray drying, making it suitable for heat-sensitive drugs.
[0069] 6. High drug loading capacity, wide range of applications, and easy to scale up industrially.
[0070] The drug content (calculated as an ion-pair complex) in the composition of this invention can reach 30%~60%, and the drug loading is significantly higher than that of conventional nanocrystalline formulations, making it suitable for preparing high-dose oral solid dosage forms. This process is applicable to various weakly acidic and weakly basic poorly soluble drugs, with strong versatility; the equipment used is all conventional equipment in the pharmaceutical industry, with a wide process parameter window and good controllability, and can be directly scaled up to industrial production, showing good prospects for industrial application. Attached Figure Description
[0071] Figure 1 This is a flowchart illustrating the preparation process of the poorly soluble drug nanocrystal composition of the present invention.
[0072] Figure 2 This is a schematic diagram of the nanocrystalline surface protective layer structure and its multiple mechanisms of action in this invention. Detailed Implementation
[0073] The present invention will be further described in detail below with reference to specific embodiments and comparative examples, but the scope of protection of the present invention is not limited thereto.
[0074] Experimental materials and instruments
[0075] 1. Experimental reagents
[0076] Itraconazole (99.5% purity, Hubei Yuancheng Pharmaceutical Co., Ltd.); Carvedilol (99% purity, Zhejiang Hisun Pharmaceutical Co., Ltd.); Ibuprofen (99% purity, Shandong Xinhua Pharmaceutical Co., Ltd.); Sodium taurine deoxycholate (NaTDC, 98% purity, Sigma-Aldrich); Cetrimonium bromide (99% purity, Aladdin Reagent Co., Ltd.); Soluplus (BASF China Co., Ltd.); Hydroxypropyl methylcellulose phthalate HP-55 (HPMCP, Shin-Etsu Chemical Co., Ltd., Japan); Hydroxypropyl... Cellulose acetate succinate HPMCASS-LF (Dow Chemical Company, USA); Vitamin E polyethylene glycol succinate (TPGS, Beijing Fengli Jingqiu Trading Co., Ltd.); L-arginine (pharmaceutical grade, Ajinomoto, Japan); Glyceryl monolaurate (pharmaceutical grade, Guangzhou Jiadelai Biochemical Technology Co., Ltd.); Trehalose (pharmaceutical grade, Hayashibara Corporation, Japan); Mannitol (pharmaceutical grade, Shandong Tianli Pharmaceutical Co., Ltd.); Glycine (analytical grade, Sinopharm Chemical Reagent Co., Ltd.); Anhydrous ethanol, acetone, dichloromethane, and other reagents were all analytical grade.
[0077] 2. Experimental apparatus
[0078] High-pressure homogenizer (AH-100D, ATS Industrial Systems Ltd.); Horizontal wet media mill (MiniCer, NETZSCH GmbH, Germany); Laser particle size analyzer (Zetasizer NanoZS90, Malvern Instruments Ltd., UK); Rotary evaporator (RE-52AA, Shanghai Yarong Biochemical Instrument Factory); Freeze dryer (LGJ-10, Beijing Songyuan Huaxing Technology Development Co., Ltd.); Laboratory spray freeze dryer (YC-3000, Shanghai Yacheng Instrument Equipment Co., Ltd.); Magnetic stirrer (85-2, Jintan Medical Instrument Factory); Electronic analytical balance (FA2004, Shanghai Precision Scientific Instruments Co., Ltd.); Dissolution tester (RCZ-6C3, Shanghai Huanghai Pharmaceutical Testing Instrument Factory); High-performance liquid chromatograph (Agilent 1260, Agilent Technologies Inc., USA); Transwell cell culture plates (Corning, USA).
[0079] Example 1: Preparation of itraconazole nanocrystal composition
[0080] Prescription composition (by dry weight parts):
[0081] Itraconazole-taurine deoxycholic acid ion pair complex: 50 parts (where the molar ratio of itraconazole to sodium taurine deoxycholic acid is 1:1)
[0082] Soluplus: 15 servings
[0083] HPMCPHP-55: 10 copies
[0084] TPGS: 5 copies
[0085] L-arginine: 4 parts
[0086] Glyceryl monolaurate: 1.5 parts
[0087] Trehalose: 18 parts
[0088] Mannitol: 9 parts
[0089] Glycine: 4.5 parts
[0090] Total: 117 samples (drug loading of approximately 28.5% and drug loading of ion-pair complexes of approximately 42.7%)
[0091] Preparation steps:
[0092] 1. Preparation of the hydrophobic ion-pair complex: 7.06 g (10 mmol) of itraconazole was weighed and dissolved in 120 mL of a dichloromethane-anhydrous ethanol (3:1 volume ratio) mixture, and stirred until completely dissolved. Separately, 5.21 g (10 mmol) of sodium taurodeoxycholate was weighed and dissolved in 40 mL of purified water. While stirring at 300 rpm, the NaTDC aqueous solution was slowly added dropwise to the itraconazole organic solution. After the addition was complete, the pH of the system was adjusted to 4.8 with 0.1 mol / L dilute hydrochloric acid, and the reaction was continued to be stirred in a 35°C water bath for 2 h. After the reaction was completed, the organic solvent was removed by rotary evaporation under reduced pressure at 40°C. The remaining aqueous suspension was pre-frozen at -50°C for 4 h and freeze-dried for 24 h to obtain a pale yellow loose powder, i.e., the itraconazole-taurodeoxycholate ion-pair complex, with a yield of approximately 95.2%.
[0093] 2. Antisolvent precipitation pre-dispersion: Weigh 5.0 g of the above ion-pair complex and dissolve it in 40 mL of anhydrous ethanol-acetone (volume ratio 1:1) mixed solvent. Stir until completely dissolved to obtain an organic solution of the complex with a concentration of 125 mg / mL. Weigh 1.5 g Soluplus, 1.0 g HPMCP, 0.5 g TPGS, 0.4 g L-arginine, and 0.15 g glycerol monolaurate and add them to 180 mL of pH 5.0 acetate buffer. Stir until completely dissolved to obtain the aqueous phase. Cool the aqueous phase to 8°C in an ice-water bath and turn on magnetic stirring to 1200 rpm. Use a syringe pump to rapidly inject the organic phase into the aqueous phase at a rate of 10 mL / min. After injection, continue stirring for 15 min to obtain a coarse nanocrystal suspension.
[0094] 3. Gradient high-pressure homogenization and refinement: The coarse nanocrystalline suspension is transferred to a high-pressure homogenizer, and the first pressure is set to 600 bar and the second pressure is set to 60 bar. The homogenization cycle is repeated 3 times. Then the pressure is increased to the first pressure to 1000 bar and the second pressure to 100 bar. The homogenization cycle is repeated 5 times. A total of 8 cycles are performed to obtain the refined nanocrystalline suspension.
[0095] 4. Spray freeze-drying curing: Add 1.8g trehalose, 0.9g mannitol, and 0.45g glycine to the refined nanocrystalline suspension, stir until completely dissolved, and bring the volume to 250mL. Transfer the suspension to a spray freeze dryer, set the feed rate to 5mL / min, atomization pressure to 0.2MPa, and refrigerant temperature to -160℃. Collect the atomized and frozen particles in a freeze tray. Transfer the tray to the freeze dryer, perform a first drying at -30℃ and a vacuum of 20Pa for 20h; perform a second drying with a gradient temperature increase to 20℃ and a vacuum of 10Pa for 6h. The discharged material is a white, loose powder, i.e., the itraconazole nanocrystalline composition.
[0096] Example 2: Preparation of Carvedilol Nanocrystalline Composition
[0097] Prescription composition:
[0098] Carvedilol-taurine deoxycholic acid ion pair complex: 45 parts (molar ratio 1:1.1)
[0099] Soluplus: 12 servings
[0100] HPMCAS-LF: 8 copies
[0101] TPGS: 4 copies
[0102] L-Lysine: 5 parts
[0103] Glyceryl monolaurate: 2 parts
[0104] Trehalose: 20 parts
[0105] Mannitol: 10 parts
[0106] Glycine: 4 parts
[0107] Preparation steps:
[0108] Following the method of Example 1, the drug was replaced with carvedilol, the ion-pairing reagent remained sodium tauride-deoxycholate, and the reaction pH was adjusted to 5.2; the temperature of the aqueous phase for antisolvent precipitation was controlled at 10°C, and the stirring rate was 1500 rpm; high-pressure homogenization was performed by cycling at 700 bar for 3 times and then at 900 bar for 5 times; the spray freeze-drying process was the same as in Example 1, to obtain the carvedilol nanocrystal composition.
[0109] Example 3: Preparation of Ibuprofen Nanocrystal Composition (Weakly Acidic Drug)
[0110] Prescription composition:
[0111] Ibuprofen-cetrimonium bromide ion-pair complex: 55 parts (molar ratio 1:0.9)
[0112] Soluplus: 10 servings
[0113] HPMCPHP-55: 8 copies
[0114] TPGS: 3 copies
[0115] L-arginine: 3 parts
[0116] Glyceryl monolaurate: 1 part
[0117] Trehalose: 15 parts
[0118] Mannitol: 7 parts
[0119] Glycine: 3 parts
[0120] Preparation steps:
[0121] Ibuprofen and cetrimonium bromide were weighed and dissolved separately at a molar ratio of 1:0.9. The pH of the mixture was adjusted to 7.0 to prepare an ibuprofen-cetrimonium bromide ion-pair complex. The subsequent antisolvent precipitation, gradient high-pressure homogenization, and spray freeze-drying steps were performed as in Example 1. The homogenization pressure was 800 bar and the cycle was repeated 6 times to obtain an ibuprofen nanocrystal composition.
[0122] Example 4: Preparation of itraconazole nanocrystals containing short-range media milling
[0123] A coarse nanocrystalline suspension was prepared according to the formulation and steps 1-2 of Example 1. After homogenization under gradient high pressure, it was transferred to a wet media mill for short-path polishing: 0.2 mm zirconia beads were filled with a filling rate of 60%, the rotation speed was 2500 rpm, the grinding temperature was 15℃, nitrogen protection was applied, and the grinding time was 20 min. After filtering to remove the beads, the product was spray-dried to obtain the final product.
[0124] Example 5: 10x Magnification Test
[0125] The formulation of Example 1 was scaled up 10 times, and antisolvent precipitation was performed using a 50L stirred tank. The mixture was then homogenized using a production-grade high-pressure homogenizer and cured using a pilot-scale spray freeze dryer. Three batches of samples were prepared consecutively to examine the process reproducibility.
[0126] Comparative Example 1: Itraconazole nanocrystals that have not formed ion pairs
[0127] The preparation steps of the ion-pair complex were omitted. 2.85g of itraconazole raw material was directly taken, and the remaining stabilizers and protectants were exactly the same as in Example 1. The same antisolvent precipitation-high pressure homogenization-spray freeze drying process was used to prepare the sample of Comparative Example 1.
[0128] Comparative Example 2: Preparation of Nanocrystals with a Single Stabilizer (Soluplus)
[0129] Only 30 parts of Soluplus were used as stabilizer. HPMCP and TPGS were removed. The rest of the formulation and preparation process were the same as in Example 1, resulting in Comparative Example 2 sample.
[0130] Comparative Example 3: Preparation of Nanocrystals with Binary Stabilizers (Soluplus + HPMCP)
[0131] The stabilizer was 18.75 parts Soluplus + 11.25 parts HPMCP (total amount was the same as in Example 1). TPGS was removed, and the rest of the formulation was the same as in Example 1. The preparation process was the same as in Example 1, and the comparative sample 3 was obtained.
[0132] Comparative Example 4: Nanocrystals without penetration enhancers
[0133] By removing L-arginine and glyceryl monolaurate, and keeping the remaining formulation and process the same as in Example 1, we obtained Comparative Example 4.
[0134] Comparative Example 5: Preparation of Nanocrystals by a Single High-Pressure Homogenization Method
[0135] The antisolvent precipitation step was omitted. The itraconazole raw material was pulverized through a 200-mesh sieve using a high-speed pulverizer and directly dispersed in an aqueous solution containing a stabilizer. The mixture was then subjected to high-speed shearing for 5 minutes to prepare a coarse suspension. The suspension was then homogenized and circulated 25 times under a pressure of 1000 bar. The rest of the process was the same as in Example 1 to obtain the Comparative Example 5 sample.
[0136] Comparative Example 6: Preparation of Nanocrystals by Single-Media Milling Method
[0137] Using the same ion-pair complex and stabilizer formulation as in Example 1, wet media milling was performed directly for 120 min, without antisolvent precipitation and high-pressure homogenization steps. The rest was the same as in Example 1, resulting in Comparative Example 6 sample.
[0138] Comparative Example 7: Preparation of solid nanocrystals by conventional spray drying
[0139] Using the same nanocrystalline suspension formulation as in Example 1, the sample was cured using a conventional spray dryer with an inlet air temperature of 120°C and an outlet air temperature of 65°C, resulting in Comparative Example 7.
[0140] Comparative Example 8: Binary freeze-drying protectant (trehalose + mannitol)
[0141] The protective agent was replaced with 2.25g of trehalose + 0.9g of mannitol (total amount was the same as in Example 1), glycine was removed, and the rest was the same as in Example 1, to obtain Comparative Example 8 sample.
[0142] Test Results and Analysis
[0143] 1. Particle size, PDI and Zeta potential determination
[0144] Take appropriate amounts of solid samples from each example and comparative example, add purified water and shake to reconstitute, then use a laser particle size analyzer to determine the average particle size, polydispersity index (PDI) and zeta potential. The measurement temperature is 25℃. Each sample is measured in parallel 3 times, and the average value is taken. The results are shown in Table 1.
[0145] Table 1. Results of particle size, PDI and Zeta potential measurements for different samples.
[0146] sheet
[0147] Example 1 168.3±4.2 0.162±0.011 -34.6±1.8 6.8 Example 2 182.5±5.1 0.175±0.013 -31.2±2.1 7.5 Example 3 156.7±3.9 0.158±0.009 +28.7±1.5 7.2 Example 4 142.9±3.5 0.145±0.008 -35.1±1.7 7.0 Comparative Example 1 325.6±12.8 0.312±0.024 -22.5±2.3 28.4 Comparative Example 2 247.8±9.6 0.268±0.021 -18.3±1.9 35.7 Comparative Example 3 201.4±6.3 0.215±0.017 -27.8±2.0 15.3 Comparative Example 4 171.2±4.5 0.168±0.012 -33.9±1.9 7.1 Comparative Example 5 268.4±8.7 0.253±0.019 -25.6±1.6 22.1 Comparative Example 6 195.3±7.2 0.227±0.018 -30.5±2.0 18.6 Comparative Example 7 386.2±15.3 0.357±0.026 -21.4±2.2 129.5 Comparative Example 8 214.7±7.8 0.234±0.016 -32.1±1.8 22.6
[0148] As shown in Table 1:
[0149] (1) The average particle size of Examples 1 to 4 of the present invention is all below 200 nm, the PDI is all less than 0.20, the particle size is small and the distribution is narrow; the absolute value of the Zeta potential is all greater than 28 mV, and the colloidal stability is good.
[0150] (2) In Comparative Example 1, no ion pairs were formed, the particle size increased significantly and the PDI increased, indicating that ion pair modification can effectively improve the adsorption effect of stabilizer and inhibit particle aggregation during the preparation process.
[0151] (3) The particle size and PDI of the single and binary stabilizer systems in Comparative Examples 2 and 3 were higher than those of the ternary system, proving that the synergistic stabilizing effect of the ternary stabilizer was better.
[0152] (4) Comparative Example 5, the single high-pressure homogenization method requires more cycles but still cannot obtain a smaller particle size. Comparative Example 6, the single medium grinding method has a wider particle size distribution, proving that the three-stage composite process of the present invention has better pulverization efficiency and particle size uniformity.
[0153] (5) After conventional spray drying, the particle size of Comparative Example 7 increased by more than 100%, resulting in severe irreversible agglomeration; the resolution effect of the binary protective agent in Comparative Example 8 was also significantly worse than that of the ternary system, proving that the combination of the ternary protective agent and spray freeze drying of the present invention can perfectly preserve the original particle size of the nanocrystals.
[0154] 2. In vitro dissolution test
[0155] Dissolution was determined according to Method II (paddle method) of General Chapter 0931, Part IV, 2020 Edition of the Chinese Pharmacopoeia. Dissolution media were pH 1.2 hydrochloric acid solution and pH 6.8 phosphate buffer, respectively, with a volume of 900 mL, a rotation speed of 50 rpm, and a temperature of 37 ± 0.5 °C. Samples equivalent to 50 mg of itraconazole from each example and comparative example were accurately weighed and added to dissolution vessels. 5 mL samples were taken at preset time points, and isothermal and equal volumes of dissolution medium were added simultaneously. The samples were filtered through a 0.22 μm microporous membrane, and the drug concentration of the filtrate was determined by HPLC to calculate the cumulative dissolution rate.
[0156] The results showed that the cumulative dissolution rate of itraconazole raw material in pH 6.8 medium was only 12.7% after 60 minutes, indicating extremely slow dissolution. The sample in Example 1 showed a cumulative release rate of only 3.8% in pH 1.2 medium after 2 hours, demonstrating good gastric acid tolerance; after being transferred to pH 6.8 medium, the cumulative dissolution rate reached 89.2% after 15 minutes and 98.5% after 60 minutes, indicating rapid and complete dissolution. The dissolution rates of Comparative Example 1 (without ion pairs) and Comparative Example 5 (single homogenized) were significantly slower than those of Example 1, proving that the particle size reduction brought about by ion pair modification and composite processes can effectively improve the dissolution rate. Comparative Example 2, without HPMCP, achieved a release rate of 42.6% in pH 1.2 after 2 hours, with no enteric effect, proving that HPMCP is key to achieving pH-responsive release.
[0157] 3. Accelerated stability assessment
[0158] Solid samples from each embodiment and comparative example were sealed and placed in a constant temperature and humidity chamber at 40°C and 75% relative humidity. Samples were taken at 0, 1, 2, 3 and 6 months, respectively. After reconstitution, the average particle size was measured and the particle size growth rate was calculated. The results are shown in Table 2.
[0159] Table 2. Particle size growth rate after 6 months of accelerated stability testing.
[0160] Example 1 168.3 183.7 9.2 Example 4 142.9 155.6 8.9 Comparative Example 1 325.6 689.2 111.7 Comparative Example 2 247.8 476.3 92.2 Comparative Example 3 201.4 312.5 55.2 Comparative Example 8 214.7 276.4 28.7
[0161] sheet
[0162] As shown in Table 2, the samples of the present invention, after being placed under accelerated conditions for 6 months, showed a particle size increase of only about 9%, demonstrating excellent physical stability. In contrast, the particle size of Comparative Example 1, which did not form ion pairs, doubled, indicating extremely poor stability. The growth rate of Comparative Example 3, which used a binary stabilizer, was also as high as 55%. This fully demonstrates that the synergistic effect of hydrophobic ion pairs and ternary stabilizers can effectively inhibit Ostwald ripening and particle aggregation, significantly improving long-term storage stability.
[0163] 4. In vitro intestinal permeability test
[0164] The intestinal permeability of the drug was evaluated using a Caco-2 cell monolayer model. Itraconazole raw material, samples from Example 1 and Comparative Example 4 were diluted to a concentration of 50 μg / mL and added to the top side (AP side) and the basal side (BL side) of a Transwell chamber, respectively. The chambers were incubated at 37°C and 5% CO2 for 2 h. The drug concentration on the BL side was measured, and the apparent permeability coefficient (Papp) was calculated. The results are shown in Table 3.
[0165] Table 3 Comparison of apparent permeability coefficients of different samples
[0166] sheet
[0167] itraconazole raw material 0.32±0.05 1.0 Comparative Example 4 (without penetration enhancer) 1.87±0.14 5.8 Example 1 2.76±0.21 8.6
[0168] The results showed that reducing the nanocrystal size alone (Comparative Example 4) could increase the permeability coefficient by 5.8 times; after adding the composite permeability enhancer (Example 1), the permeability coefficient was further increased to 8.6 times, proving that the synergistic effect of L-arginine, glycerol monolaurate and TPGS can significantly enhance the intestinal permeability of drugs.
[0169] 5. In vivo pharmacokinetic studies
[0170] Twenty-four healthy male SD rats, weighing 220±20g, were randomly divided into three groups of eight each. Rats were fasted for 12 hours prior to the experiment but allowed free access to water. The rats were administered itraconazole raw material suspension, Comparative Example 4 sample, and Example 1 sample by gavage at a dose of 25 mg / kg (calculated as itraconazole). Blood samples were collected from the orbital venous plexus at 0.25, 0.5, 0.75, 1, 1.5, 2, 3, 4, 6, 8, 12, and 24 hours after administration. The blood was anticoagulated with heparin, and plasma was separated by centrifugation. Plasma drug concentration was determined by HPLC-MS / MS, and pharmacokinetic parameters were calculated using DAS2.0 software.
[0171] Table 4. Pharmacokinetic parameters in rats
[0172] sheet
[0173] Cmax(ng / mL) 42.6±8.3 168.5±21.7 298.7±32.5 Tmax(h) 2.5±0.5 1.5±0.3 1.0±0.2 <![CDATA[AUC 0-24 (ng·h / mL)]]> 268.4±45.2 1056.3±98.6 2145.8±176.4 Relative bioavailability (%) 100 393.6 799.4
[0174] The results showed that the Cmax and AUC of Example 1 were 7.0 times and 8.0 times that of the active pharmaceutical ingredient, respectively, with a nearly 7-fold increase in bioavailability, significantly better than Comparative Example 4 without a permeation enhancer. This is attributed to the synergistic effect of the small particle size rapid dissolution, pH-responsive intestinal targeted release, and multiple permeation-enhancing mechanisms of the present invention.
[0175] 6. Results of process scale-up verification
[0176] The average particle sizes of the three batches of scaled-up samples in Example 5 were 170.2 nm, 167.5 nm, and 172.1 nm, with an inter-batch RSD of 1.3%; the PDI were 0.165, 0.160, and 0.169, with an inter-batch RSD of 2.7%, all of which showed no significant difference from the laboratory small-scale samples. This demonstrates that the process of the present invention has good reproducibility, small scale-up effect, and has the potential for industrial production.
[0177] In summary, this invention, through multiple technological innovations including hydrophobic ion modification at the source, ternary functional composite stabilizers, a three-stage synergistic preparation process, composite permeation promoters, and a ternary freeze-drying protection system, has successfully prepared a poorly soluble drug nanocrystal composition with small particle size, narrow distribution, high stability, rapid dissolution, high bioavailability, and pH-responsive enteric coating properties. This effectively solves many bottleneck problems existing in the prior art and has significant technological progress and good application prospects.
[0178] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A poorly soluble drug nanocrystal composition, characterized in that: The composition comprises the following components in parts by dry weight: (1) Hydrophobic ion pair complex: 30-60 parts, wherein the hydrophobic ion pair complex is formed by the combination of a poorly soluble drug and a hydrophobic ion pair reagent through ionic bonds, and the molar ratio of the two is 1:0.5-1.5; (2) Ternary functional composite stabilizer: 10-35 parts, wherein the ternary functional composite stabilizer is composed of amphiphilic block copolymer, enteric cellulose derivative and functional nonionic surfactant in a mass ratio of 1:0.3-1:0.2-0.5; (3) Composite penetration enhancer: 2-8 parts, composed of basic amino acids and medium-chain fatty acid monoglycerides in a mass ratio of 2-4:1; (4) Ternary composite freeze-drying protectant: 20-50 parts, composed of trehalose, mannitol and glycine in a mass ratio of 2-4:1-2:0.5-1; The composition is in solid powder form, and after reconstitution, the average particle size of the nanocrystals is 80-220 nm, the polydispersity index (PDI) is ≤0.20, and the absolute value of the zeta potential is ≥30 mV.
2. The poorly soluble drug nanocrystal composition according to claim 1, characterized in that: The poorly soluble drug is a Class II or Class IV drug in the Biopharmaceutics Classification System, selected from any one of itraconazole, ketoconazole, posaconazole, carvedilol, cinnarizine, loratadine, aprepitant, rilpivirine, atorvaquinone, celecoxib, diclofenac, indomethacin, ibuprofen, furosemide, and naproxen.
3. The poorly soluble drug nanocrystal composition according to claim 1, characterized in that: The hydrophobic ion-pairing reagent is selected from any one or more combinations of cholic acid, deoxycholic acid, taurideoxycholic acid, glycodeoxycholic acid, sodium dodecyl sulfate, stearic acid, oleic acid, cetrimonium bromide, arginine dodecyl ester, and choline stearate, and is selected according to the charge properties of the poorly soluble drug.
4. The poorly soluble drug nanocrystal composition according to claim 1, characterized in that: The amphiphilic block copolymer is a polyvinylcaprolactam-polyvinyl acetate-polyethylene glycol graft copolymer; the enteric cellulose derivative is selected from any one or a combination of two of hydroxypropyl methylcellulose phthalate and hydroxypropyl methylcellulose acetate succinate; the functional nonionic surfactant is vitamin E polyethylene glycol succinate.
5. The poorly soluble drug nanocrystal composition according to claim 1, characterized in that: The basic amino acid is selected from any one of L-arginine, L-lysine, and L-histidine; the medium-chain fatty acid monoglyceride is glycerol monolaurate.
6. A method for preparing the poorly soluble drug nanocrystal composition according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: React the poorly soluble drug with the hydrophobic ion-pairing reagent in a solvent, and then dry to obtain a hydrophobic ion-pairing complex powder; Step 2: Dissolve the hydrophobic ion pair complex in a good solvent as the organic phase, dissolve the ternary functional composite stabilizer and composite penetration enhancer in an aqueous medium as the aqueous phase, inject the organic phase into the aqueous phase for anti-solvent precipitation, and obtain a coarse nanocrystal suspension. Step 3: The coarse nanocrystal suspension is subjected to high-pressure homogenization to obtain a refined nanocrystal suspension; Step 4: Add a ternary composite freeze-drying protectant to the refined nanocrystal suspension, and then freeze-dry by spray to obtain a solid poorly soluble drug nanocrystal composition.
7. The preparation method according to claim 6, characterized in that, In step 2, the volume ratio of the organic phase to the aqueous phase is 1:5 to 15, the temperature of the aqueous phase is 4 to 15°C, and the injection rate is 5 to 20 mL / min. In step 3, the high-pressure homogenization adopts a gradient pressure increase strategy, first homogenizing 2 to 4 times at a pressure of 500 to 700 bar, and then homogenizing 3 to 8 times at a pressure of 800 to 1200 bar.
8. The preparation method according to claim 6, characterized in that, After step 3 and before step 4, a short-range media grinding and polishing step is also included: the refined nanocrystalline suspension is transferred to a wet media grinding machine, using zirconia grinding beads with a diameter of 0.1 to 0.3 mm, a grinding speed of 2000 to 3000 rpm, a grinding temperature of 5 to 25°C, and a grinding time of 15 to 30 min.
9. The preparation method according to claim 6, characterized in that, In step 4, the process parameters for spray freeze drying are as follows: feed rate 2-10 mL / min, atomizing gas pressure 0.15-0.3 MPa, refrigerant temperature -196 to -120℃; shelf temperature in the first drying stage -35 to -20℃, vacuum degree 10-30 Pa, drying time 12-36 h; shelf temperature in the second drying stage increases to 10-25℃ at a rate of 2-5℃ / h, vacuum degree 5-15 Pa, drying time 4-10 h.
10. The preparation method according to claim 6, characterized in that, In step 1, the solvent is an organic solvent and water or a water-organic mixture, the reaction temperature is 30-45℃, and the reaction time is 1-3h.